Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.7326/0003-4819-142-1-200501040-00006
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Self-Management of Oral Anticoagulant Therapy with Clinic Management

Abstract: Compared with conventional management by an anticoagulation clinic, self-management of oral anticoagulant treatment achieved a similar level of control. Of note, major complications and minor hemorrhages were less common in the self-management group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
161
4
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(187 citation statements)
references
References 30 publications
15
161
4
5
Order By: Relevance
“…We hypothesize it is these preferences that account for the high drop-out rate experienced (up to 20%) in previous self-management trials. 4,7 Subsequent economic analysis should stratify cost-effectiveness by indication and by preference for using the point-ofcare device. This will aid in informing clinicians and decision-makers on which patients are most likely to benefit from self-management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize it is these preferences that account for the high drop-out rate experienced (up to 20%) in previous self-management trials. 4,7 Subsequent economic analysis should stratify cost-effectiveness by indication and by preference for using the point-ofcare device. This will aid in informing clinicians and decision-makers on which patients are most likely to benefit from self-management.…”
Section: Discussionmentioning
confidence: 99%
“…4 Several published trials have compared self-management with physician management or management in an anticoagulation clinic. [4][5][6][7][8][9][10][11][12][13] It has been found that patients who self-manage check their INR more frequently and are able to maintain a greater proportion of INRs within the therapeutic range compared with those whose therapy is monitored by a physician or in an anticoagulation clinic. [11][12][13] The results of a recent meta-analysis showed a significant reduction in thromboembolic events (odds ratio [OR] 0.45), major hemorrhagic events (OR 0.65) and all-cause mortality (OR 0.61) for those using a self-management or self-test strategy.…”
mentioning
confidence: 99%
“…55,57,[61][62][63][64][65] In 11 trials, the randomisation process proved to be adequate but no information was provided on the way in which participants were allocated to the study interventions. 58,60,[66][67][68][69][70][71][72][73][74] One trial 75 reported adequate details about the generation of the random sequence but failed to conceal the allocation of participants to study interventions.…”
Section: Selection Biasmentioning
confidence: 99%
“…Six of them had limited missing data with similar reasons for discontinuation across intervention groups. 59,69,72,74,76,79 Seven trials relied on an intention-to-treat approach and all dropouts were fully accounted for in the statistical analyses, 55,61,[63][64][65]71,75 while the other four reported no missing data. 58,60,62,78 Eight of the 26 included trials were at high risk of attrition bias, with more than 5% dropout rate and with missing data not appropriately tackled.…”
Section: Selection Biasmentioning
confidence: 99%
See 1 more Smart Citation